Characterization of adipokinetic hormone receptor in stick insect, Carausius Morosus - Sınmaz, Merve Gizem. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
Adipokinetic hormone (AKH) is an insect neuropeptide and known as gonadotropinreleasing hormone, which is orthologue to humans. It is released from corpora cardiaca and acts generally on fat body for energy mobilization. It is also involved in several different physiological functions such as increasing blood hemolymph trehalose levels, heart beat frequency, and protein synthesis. Furthermore it functions in inhibiting fatty acid and RNA synthesis in different insect species. It activates its corresponding G-Protein Coupled Receptors (GPCR), which are Adipokinetic Hormone receptors (AKHR). Many AKHRs were studied so far, but not in stick insect, Carausius morosus. Utilizing transcriptome data of stick insect, its AKHR (CamAKHR) and AKH (CamAKH) were identified. It was aimed to characterize AKHR of stick insect by homology modeling, docking analysis and molecular dynamics within this project contributing to the production of a novel neuropeptide-based next-generation pesticide. At the end, thirteen important residues mostly located in transmembrane 6, transmembrane 7 and extracellular loop 2 regions of CamAKHR model were observed contributing to ligand binding in CamAKHR- CamAKH complex. Six of them were found as the most conserved residues in different insect species, therefore proposed binding pocket includes these Glu246, Arg269, Tyr423, Tyr430, Lys446 and Phe449 residues corresponding to TM2, TM3, TM6 and TM7 of CamAKHR.
Keywords: Carausius morosus.